Bottom-up cost evaluation of SOEC systems in the range of 10–100 MW. (8th November 2018) - Anghilante, Régis; Colomar, David; Brisse, Annabelle; Marrony, Mathieu
Abstract: A detailed bottom-up cost evaluation of SOEC systems in the range of 10–100 MW was carried out based on recent experimental results in the SOEC field. Capital costs of installed SOEC systems were evaluated starting from raw SOEC materials. Two scenarios were defined, assuming different capacities of SOEC units, yearly production capacities of SOEC cells and stacks as well as operating conditions of manufacturing lines. It resulted in installed capital costs of 309–395 €/kW for SOEC units integrated into power-to-methane plants (reference case) and of 380–494 €/kW for stand-alone SOEC units. This highlights the cost reduction potential of the SOEC technology when thermally coupled with a steam source. These costs were compared with previous capital cost estimates for future SOEC, proton exchange membrane (PEM) and alkaline electrolysis systems available in the literature. A sensitivity analysis allowed to identify which parameters have the highest impact on installed system costs. In the least favorable conditions, it was estimated that they could raise up to 494–618 €/kW for SOEC units in the reference case and up to 573–727 €/kW for stand-alone SOEC units. Highlights: Bottom-up cost evaluation of SOEC systems starting from raw SOEC materials. Cost breakdowns at cell, stack and system level are provided. Sensible cost reduction through production scale-up and automation is observed. Capital costs calculated for SOEC units integrated into a power-to-methane plant or as stand-alone units. Capital costs could raise up to 494–727 €/kW according to worst case scenario.